Survey-Based Intelligent Tutoring System (ITS) to Support Emotional and Sentiment Analysis in Education - Yugal, Lisha; Kaswan, Suresh; Bhatia, BS (International Journal of Computer Sciences and Engineering, 2023)
This article delves into the evolving landscape of education technology, with a particular focus on Intelligent Tutoring Systems (ITS). These systems have redefined the educational experience by harnessing the power of artificial intelligence and machine learning to deliver personalized and adaptive learning journeys. While traditional ITS prioritize academic performance, a burgeoning realm of research is exploring the integration of emotional and sentiment analysis into these systems. This article navigates this frontier, shedding light on a novel approach—the survey-based ITS. This innovative concept seeks to support emotional and sentiment analysis within the educational context, emphasizing its potential significance and transformative impact on the field of education. Moreover, this article acknowledges the pivotal role that emotional intelligence (EI) plays in a student`s holistic development and learning trajectory. EI encompasses a spectrum of abilities, including the capacity to recognize, comprehend, and regulate one`s own emotions, as well as those of others. In the educational milieu, cultivating emotional intelligence is essential for fostering a positive and effective learning environment. By seamlessly incorporating emotional analysis into Intelligent Tutoring Systems, educators can gain invaluable insights into students` emotional states, paving the way for more precise and empathetic support. In this regard, this article strives to unveil the multifaceted facets of emotional intelligence in education, underlining its profound significance and offering practical strategies for seamless integration.